A FIRST‐ORDER BSPDE FOR SWING OPTION PRICING. (20th May 2014) - Bender, Christian; Dokuchaev, Nikolai
Abstract: We study an optimal control problem related to swing option pricing in a general non‐Markovian setting in continuous time. As a main result we uniquely characterize the value process in terms of a first‐order nonlinear backward stochastic partial differential equation and a differential inclusion. Based on this result we also determine the set of optimal controls and derive a dual minimization problem.